Toilet School for Children with Failure to Toilet Train: Comparing a Group Therapy Model with Individual Treatment. Issue 3 (April 2016) - Law, Evelyn; Yang, Jeffrey H.; Coit, Margaret H.; Chan, Eugenia
ABSTRACT: Objective: This study compared the toileting outcomes of children participating in Toilet School group therapy with children in individual treatment. Method: All children in this study failed conventional toilet training and were 4 to 6 year, 11 month old. Cases were 63 children who attended a 6-week Toilet School group therapy with their parents. Controls were 62 children who were seen in individual treatment in the same tertiary care program and were matched to cases based on treatment dates. We analyzed the number of toileting benchmarks met for cases and controls. We used a stepwise linear regression model to investigate the contribution of child and family factors in predicting the number of toileting benchmarks met. Results: Compared to controls, cases achieved significantly more toileting benchmarks ( p < .001) at the end of Toilet School, were more likely to have bowel movements in the toilet ( p = .001), and required fewer subsequent visits until completion of toilet training ( p = .013). Similarly, at the seventh provider encounter for both controls and cases, the cases continued to achieve significantly more toileting benchmarks ( p < .001) and were more likely to have bowel movements in the toilet ( p = .002) compared to controls. After adjusting for age, gender, neighborhood poverty level, and number of total clinical visits for fecal incontinence, treatment grouping was the only independent variable that predicted toileting progress. Conclusion: For children with failure to toilet train, group treatment involving both the child and the family results in greater improvement in toileting outcomes than individual treatment.